Balloon Therapy to Reduce Shortness of Breath in Chronic Obstructive Lung Disease Patients - Khoiriyah Khoiriyah; Farida Adi Rahayu; Tri Nurhidayati; Arief Shofyan Baidhowy (Universitas Aisyah Pringsewu, 2022)
Blowing the Balloon makes lung expansion and improves intercostal muscles. This process helps patients with COPD remove trapped carbon dioxide in the lungs. Management of COPD requires comprehensive treatment, both pharmacologically and non-pharmacologically. Balloon therapy is a non-pharmacological therapy to reduce shortness of breath. The purpose of this study is to analyze the effect of balloon therapy on reducing shortness of breath in COPD patients at PKU Muhammadiyah Temanggung Hospital. The design was used a Quasi-experiment research type one group pre-test post-test without a control group with 36 respondents using a simple random sampling technique. Measure the degree of shortness of breath using the Modified Medical Research Council Scale questionnaire. Ballon therapy intervention was carried out using breathing exercises by blowing a balloon until the balloon inflated with a diameter of 7 inches about 5 times per day for 14 days. The statistical test used the Wilcoxon signed-rank test. The results showed decreased shortness of breath in COPD patients before and after balloon therapy intervention. The average measurement result of the degree of shortness of breath on the first day was around 2.50, while on the 7th day it was 1.89, and on the 14th day of measurement, the average degree of shortness of breath was 1.06. There is an effect of balloon therapy in reducing shortness of breath in COPD patients in the pulmonary poly ward of PKU Muhammadiyah Temanggung Hospital with a p-value of 0.000 (p less than 0.005). Nurses are expected to provide education about balloon therapy to reduce the degree of COPD shortness of breath. The results of this study show that balloon therapy is effective in reducing shortness of breath in COPD patientsAbstrak: Meniup Balon membuat ekspansi paru-paru meningkatkan otot interkostal. Proses ini membantu pasien PPOK mengeluarkan karbon dioksida yang terperangkap di paru-paru. Penatalaksanaan PPOK memerlukan penanganan yang komprehensif, baik secara farmakologis maupun nonfarmakologis. Terapi balon merupakan terapi nonfarmakologis untuk mengurangi sesak napas. Tujuan penelitian ini adalah menganalisis pengaruh terapi balon terhadap penurunan sesak napas pada pasien PPOK di RS PKU Muhammadiyah Temanggung. Rancangan penelitian yang digunakan adalah Quasi-experiment one group pre-test post-test tanpa kelompok kontrol dengan 36 responden menggunakan teknik simple random sampling. Pengukuran derajat sesak napas menggunakan kuesioner Modified Medical Research Council Scale. Intervensi terapi balon dilakukan dengan menggunakan latihan pernapasan dengan cara meniup balon hingga balon yang berdiameter 7 inci sebanyak 5 kali per hari selama 14 hari. Uji statistik menggunakan uji Wilcoxon. Hasil penelitian menunjukkan terdapat penurunan sesak napas pada pasien PPOK sebelum dan sesudah diberikan intervensi terapi balon. Hasil pengukuran rata-rata derajat sesak nafas pada hari pertama adalah sekitar 2,50 pada hari ke-7 sebesar 1,89 dan pada pengukuran hari ke-14 didapatkan rata-rata derajat sesak nafas sebesar 1,06. Ada pengaruh terapi balon dalam menurunkan sesak napas pada pasien PPOK di poli paru RS PKU Muhammadiyah Temanggung dengan p-value 0,000 (p kurang dari 0,005). Perawat diharapkan memberikan edukasi tentang terapi balon untuk menurunkan derajat sesak nafas PPOK. Hasil penelitian ini menunjukkan bahwa terapi balon efektif dalam mengurangi sesak napas pada pasien PPOK